Evaluation of Blood Supplement Tablet Distribution at Community Health Centers (Puskesmas) in Sleman Regency - Candra Sari, Veronika Yuni; Puspandari, Dyah Ayu; Widayanti, Anna Wahyuni (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Anemia is a condition often found in adolescent girls and pregnant women in developing countries. The government has made efforts to reduce cases of anemia through a program that provides blood supplement tablets to teenage girls and pregnant women. However, the distribution coverage in Sleman is still 85%.Objectives: This study aimed to determine how to distribute blood supplement tablets from the community health center.Methods: This research used a qualitative approach, data collection techniques with interviews, and observation of the document distribution process in 2022. The study was conducted using purposive sampling, and 35 respondents were health workers, teachers, pregnant women, and female students. The interview results were analyzed using content analysis.Results: The results of the observation document show that only one of the five indicators is still below standard: TOR, at Puskesmas A is 0,72 times, and at Puskesmas B is 0,44 times. The availability in Puskesmas B is 27 months. The supporting factors in the distribution are regulations, educating pregnant women, and the availability of blood supplement tablets. The inhibiting factors in the distribution process are the need for more budget for distribution to schools, the lack of schedule for distribution and taking blood supplement tablets together in schools, and the lack of education of health workers for teachers and female students.Conclusion: The process of distributing blood supplement tablets at the community health center in Sleman Regency is efficient and according to the guidelines for administering blood supplement tablets to pregnant women and female students.